Burden of Parkinson's Disease by Severity: Health Care Costs in the U.S. Medicare Population. Issue 1 (8th October 2020) - Dahodwala, Nabila; Li, Pengxiang; Jahnke, Jordan; Ladage, Vrushabh P.; Pettit, Amy R.; Kandukuri, Prasanna L.; Bao, Yanjun; Zamudio, Jorge; Jalundhwala, Yash J.; Doshi, Jalpa A.
ABSTRACT: Background: Current understanding of the health care costs of Parkinson's disease (PD) and the incremental burden of advanced disease is incomplete. Objectives: The aim of this study was to assess the direct economic burden associated with advanced versus mild/moderate PD in a prevalent national sample of elderly U.S. Medicare beneficiaries with a PD diagnosis. Methods: Analyzing 100% fee‐for‐service Medicare claims from 2013, we defined advanced PD with a medication‐based algorithm and calculated all‐cause and PD‐related costs for the overall sample and by disease severity. We measured primary PD‐related costs (based on claims with a primary diagnosis of PD) and any PD‐related costs (based on claims with PD in any diagnostic field). Generalized linear models were used to estimate risk‐adjusted mean cost differences between the advanced and mild/moderate PD groups for the calendar year. Results: The final sample (N = 144, 703) had mean observed all‐cause, primary PD‐related, and any PD‐related costs of $23, 041 (SD, $34, 045), $3429 (SD, $7431), and $9924 (SD, $22, 140), respectively. Twenty percent of patients were classified as advanced PD. Costs varied substantially; any PD‐related mean costs were $483 for the lowest patient decile (which included 1% of the advanced group) and $48, 145 for the highest decile (which included 15% of the advanced group). Incremental risk‐adjusted costs of advanced PD were $5818 (95% confidence interval [CI]: $5411–$6225) for all‐cause costs, $3644 (95% CI: $3484–$3806) for primary PD‐related costs, and $6088 (95% CI: $5779–$6398) for any PD‐related costs. Conclusions: Elderly Medicare beneficiaries with PD had substantial variation in PD‐related costs. Advanced PD was associated with a larger economic burden than mild/moderate PD. © 2020 International Parkinson and Movement Disorder Society